A comparison of domain decomposition techniques for analysing disjoint finite antenna arrays - Ludick, D.; Maaskant, R.; Davidson, David; Jakobus, U.; Mittra, R. (2014)
© 2014 European Association on Antennas and Propagation. The purpose of this work is to present a quantitative comparison between three Method-of-Moments based domain decomposition techniques that are used for the analysis of large, disjoint finite antenna arrays. The methods considered are the Characteristic Basis Function Method, the Domain Green's Function Method, and a newly proposed improved version of the DGFM, i.e., the i-DGFM. The computational complexities of the techniques are compared in terms of runtime and memory usage. Both active and passive antenna arrays are considered.